Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1159/000284767
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Thought Disorder in Manic Psychosis

Abstract: Twenty-two patients with mania were evaluated for a variety of psychiatric phenomena. These items along with demographic data were used to predict relapse over a 36-month period in a multiple regression model. Formal thought disorder at the onset of illness was a strong predictor of relapse (F = 39, p < 0.001). The quality of the thought disorder was the most significant prognostic indicator. The predictive value of negative thought disorder was not enhanced by the addition of other symptomatic or demographic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Moodincongruent psychotic symptoms have also been associated with higher Brief Psychiatric Rating Scale scores 6 months after the index manic episode, and worse Global Assessment of Functioning scores 2 years after a manic episode [22]. Formal thought disorder during the acute episode has been associated with a shorter time in remission and increased rates of relapse [67]. Schneiderian first-rank psychotic symptoms may be associated with a poor response to lithium monotherapy [68] and poor residential status [23].…”
Section: Prognostic Implications Of Psychosis In Maniamentioning
confidence: 99%
“…Moodincongruent psychotic symptoms have also been associated with higher Brief Psychiatric Rating Scale scores 6 months after the index manic episode, and worse Global Assessment of Functioning scores 2 years after a manic episode [22]. Formal thought disorder during the acute episode has been associated with a shorter time in remission and increased rates of relapse [67]. Schneiderian first-rank psychotic symptoms may be associated with a poor response to lithium monotherapy [68] and poor residential status [23].…”
Section: Prognostic Implications Of Psychosis In Maniamentioning
confidence: 99%
“…Loosening of associations, clanging, repetitive and concrete speech, and poverty of speech are some of the forms of thought disorder that have been observed in manic and depressed patients (Grossman & Harrow, 1991). Wilcox (1992) found that the quality of formal thought disorder was a strong predictor of relapse in manic patients. However, there has been relatively little research on the degree to which thought disorder occurs in other phases of the illness.…”
Section: Introductionmentioning
confidence: 99%
“…Psychosis has been found to be associated with linguistic deficits [1][2][3] and poorer social and clinical outcomes [4,5]. The central role of language in the development of schizophrenia (SKZ) has been first hypothesized by Crow [6] who correlated the origin of psychotic symptoms with an altered hemispheric lateralization [7].…”
Section: Introductionmentioning
confidence: 99%
“…; z = -9.2 HCsvsFEP-NA; p < 0.001 FEP-NA = FEP-A> HCs HCsvsFEP-A; z = -4 4. HCsvsFEP-A; p < 0.001 FEP-NAvsFEP-A; z = 2.AE 0.8 HCsvsFEP-NA; z = -8.2 HCsvsFEP-NA; p < 0.001 FEP-NA = FEP-A> HCs HCsvsFEP-A; z = -3.9HCsvsFEP-A; p = 0.002 FEP-NAvsFEP-A; z = 2.AE 0.6 HCsvsFEP-NA; z = -5.8 HCsvsFEP-NA; p < 0.001 FEP-NA = FEP-A > HCs HCsvsFEP-A; z = -3.5 HCsvsFEP-A; p = 0.01 FEP-NAvsFEP-A; z = 0.6 FEP-NAvsFEP-A; p = 1 TCGB Passive Affirmative Item 0.5 AE 1.1 0.2 AE 0.4 0.1 AE 0.4 HCsvsFEP-NA; z = -4.3 HCsvsFEP-NA; p < 0.001 FEP-NA > FEP-A and HCs HCsvsFEP-A; z = -0.4 HCsvsFEP-A; p = 1 FEP-NAvsFEP-A; z = 3.-NAvsFEP-A; p = 1 FEP-A = Affective First Episode psychosis; FEP-NA = Non-affective First Episode Psychosis; HCs = Healthy Controls; TCGB = Test di Comprensione Grammaticale per Bambini.…”
mentioning
confidence: 97%